Improvements in Insulin Resistance and Glucose Metabolism Related to Breastfeeding Are Not Mediated by Subclinical Inflammation - Julia Martins de Oliveira; Patrícia Médici Dualib; Alexandre Archanjo Ferraro; Rosiane Mattar; Sérgio Atala Dib; Bianca de Almeida-Pititto (Metabolites)
Background: Lactation is known to improve insulin resistance, but this phenomenon remains poorly understood. Our goal was to evaluate whether subclinical inflammation could mediate the association between breastfeeding (BF) and improvement in glucose metabolism and markers of insulin resistance (MIRs) in the postpartum. Methods: A total of 95 adult women (≥18 years) with a BMI ≥ 25 kg/m2 from the outpatient clinic of the Federal University of São Paulo were followed from early pregnancy until 60 to 180 days postpartum. The patients were divided based on their BF status: BF and non-BF groups. A latent variable termed SubInf was created incorporating inflammation-related biomarkers: adiponectin, E-selectin, branched-chain amino acids, zonulin, copeptin, and lipopolysaccharides. The association of BR with MIRs in the postpartum was evaluated through linear regression analysis, and mediation analysis was performed to evaluate the role of SubInf in this association. Results: The groups were similar regarding gestational diabetes mellitus (GDM) prevalence, pre-gestational BMI, caloric intake, physical activity, and postpartum weight loss. The BF group presented lower levels of triglycerides (TGs), fasting glucose, fasting insulin, TG/HDLcholesterol ratio (TG/HDL), TyG index, and HOMA-IR compared to the non-BF group. A linear regression analysis adjusted for scholarity, parity, pre-gestational BMI, GDM, weight gain during pregnancy, and mode of delivery revealed an inverse association between BF and fasting glucose [−6.30 (−10.71 to −1.89), p = 0.005), HOMA-IR [−0.28 (−0.50 to −0.05), p = 0.017], TyG index [−0.04 (−0.06 to −0.01), p = 0.002], and TG/HDL ratio [−0.23 (−0.46 to −0.01), p = 0.001]. In the mediation analysis, SubInf did not mediate the indirect effect of BF on MIRs. Conclusions: In overweight and obese women, an association between BF and improvement in MIRs in the postpartum was seen, corroborating that BF should be stimulated, especially in these cardiometabolic high-risk women. Subclinical inflammation did not seem to mediate this association.